Caracterização de uvas de mesa e estratégias para manutenção da qualidade durante o armazenamento de cachos e de bagas destacadas - Soldateli, Francis Júnior (2022)
With the release of new table grapes hybrid cultivars, with greater adaptability and tolerance to pests in relation to the ‘Italia’ group, there is a growing interest in the cultivation of grapes intended for fresh consumption in the South region. However, the harvest is concentrated in a short period of the year, increasing dependence on table grapes from other growing regions during the off-season. In this sense, the adoption of storage systems that maintain the quality for long periods can benefit local production and expand the supply of grapes. In addition, marketing in the form of detached berries can increase the use of grapes with low commercial value and eliminate some inconveniences found in bunches marketing. The objective of this study was to characterize the quality of the new table grape cultivars ‘BRS Nubia’ and ‘BRS Isis’, and the traditional ‘Italia’ produced in temperate climates, and to evaluate the effects of different techniques during cold storage, on the quality maintenance of the grapes in the form of detached berries and bunches. The first manuscript characterized ‘BRS Nubia’, ‘BRS Isis’, and ‘Italia’ table grapes quality, produced on Serra Gaúcha region. The second manuscript evaluated the storage of these cultivars in the form of detached berries for 30 and 60 days (0.5 °C), in the following conditions: [1] control; [2] sulfur dioxide (SO2) (1.5 g Na2S2O5 per kg-1 of grape); [3] ethanol solution (30% for 5 min); [4] hot water (50 °C for 10 min) and [5] 1methylcyclopropene (1-MCP) (2.0 μL L-1). The third manuscript highlighted the storage of ‘BRS Isis’ table grapes for 60 and 90 days (0.5 °C) under the following conditions: [1] control; [2] SO2; [3] 1,125 ppm ethanol; [4] 2,250 ppm ethanol; [5] 10 kPa of CO2 and [6] 15 kPa of CO2. ‘BRS Nubia’ and ‘BRS Isis’ grapes showed higher concentrations of bioactive compounds than ‘Italia’, especially ‘BRS Nubia’ with higher content of anthocyanins in the skin. ‘Italia’ presented berries with high concentrations of volatile compounds, especially terpenes that give the moscato aroma. The cultivars showed a good storage potential in the form of detached berries when associated to SO2, ethanol or hot water treatment. Hot water was effective on decay incidence control and suppressed the degradation of grapes up to 30 days. SO2 and ethanol allowed the table grapes quality maintenance for up to 60 days. Ethanol showed similar results to SO2 in the decay control. However, ethanol and hot water treatments increased the cracking incidence in ‘BRS Isis’ grapes. Ethanol also increased the cracking on the berries of this cultivar stored in the bunch form. The storage with 15 kPa of CO2 and 2,250 ppm of ethanol presented similar efficiency to SO2 in the decay control during storage for up to 90 days. However, the ethanol treatment resulted in acetaldehyde accumulation, which can result in offflavors to the grapes. High CO2 concentrations maintained higher concentrations of phenolic compounds and volatile compounds hexanal and (E)-2-hexenal, indicating a better quality of the grapes.